CHINA ACTION IN WATERS AROUND NATUNA, A CHALLENGE TO INDONESIA’S BLUE ECONOMY SOVEREIGNTY (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Southeast Asia nations have experienced several confrontations with China in waters around “South China Sea”. In 2020, Indonesia lodged a protest to the United Nations regarding China’s action of placing dozens of Chinese fishing vessels with coast guard on waters near Natuna Island. China claimed the location as its sovereignty using a traditional “Nine Dash Line” argument. Indonesia then countered with placing warships and F-16 fighter to patrol the region. This article analyses the event using politico-historical approach to understand the characteristic of China’s behavior. China had developed into modern country with strong confident nature. Its strong economic development compared to those of the Southeast Asia nations allegedly played role in policing the action. China’s Belt and Road Initiatives (BRI) project which collaborated with around 120 countries made it stronger in its global influence. With this superiority, China could be thinking that Southeast Asia nations will weaken its stance if facing a conflict with the country. However, in the incident in the waters around Natuna in 2020, Indonesia took a “no compromise” stance – different from that of other neighbouring Southeast Asian country had taken - clearly marked the balancing strategy. This action can be said as a sturdy effort to secure Indonesia’s Blue Economy plan.
Keywords: Natuna Island; South China Sea; China; Indonesia; Hedging strategy